The Cultural and Pragmatic Potential of the “Phraseological Worldview” in the Kazakh Language (Eurasian Journal of Philology Science and Education, 2025)
The problem of «man in language», which underlies the research process of the modern anthroposubject paradigm, requires a comprehensive research system of language recognition. In this regard, the study of the natural nature of language as a cognitive, social, cultural phenomenon in conjunction with the «image of the universe», in which the knowledge of the language owner about the world is formed, is of great importance. Ethnolinguistic, linguocultural, lingovosocial, etc. the results of the comprehensive research of the school of Academician A. T. Kaidar in the anthropocentric direction, based on the continuity of language этн Ethnos (people) мәдениет culture, language табиғат nature in Kazakh linguistics, are known. The article will focus on the problem of the formation of cognitive phraseology in Kazakh linguistics, based on the research of the representative of this school, phraseologist-scientist G. Smagulova, conducted on the basis of new directions and paradigms of linguistic linguistics.In connection with this, the system of research conducted in order to characterize the «phraseological picture» of the Kazakh world is evaluated at the level of modern linguistics by a scientist who adheres to the principle of «national code», which corresponds to the linguocognitive level of language research in modern linguistics, which defines Kazakh phraselogy according to linguistic paradigms. Such studies make it possible to better understand the unity of language and culture and to interpret national identity from a cognitive perspective.Key words: Phraseological world, cognitive phraseology, language, ethnicity (person), culture, language.Keywords: nature, national code, linguistic and sociological analysis, cultural communication, anthropogenic paradigm, zoomorphisms, somatisms, phraseological units